The Prophylactic Use of Lipid Emulsion Therapy in the Excision of Invasive Malignant Melanoma under Local Anaesthetic in a Morbidly Obese Patient - K. S. Sharma; P. Lim; T. M. Brotherston; P. Smith (Case Reports in Surgery)
We present the first reported case of the prophylactic use of lipid emulsion therapy in the removal of an extensive, circumferential malignant melanoma in a morbidly obese patient, under local anaesthetic. The advantages of this technique allowed the patient to avoid intraoperative invasive monitoring and postoperative critical care admission and assisted during the operation by rotating her leg when needed. This is a useful technique that can be employed in urgent cases where there is a need to excise extensive skin malignancies in patients who are unsuitable for general or regional anaesthesia.